Spatiotemporal Variations of Human Pressure on Key Biodiversity Areas in the Qinghai–Tibet Plateau: A Comparative Analysis - Zeng, Yuxi; Wang, Ling-en; Zhong, Linsheng (Frontiers in Ecology and Evolution, 2022)
A key biodiversity area (KBA) is one of the important emerging area-based conservation measures that is being implemented recently in China; however, the human pressure faced by a KBA is still unclear. This study analyzed the spatiotemporal variation of human pressure on KBAs from 1990 to 2017 and compared it with the human pressure on national natural reserves (NNRs) through a case study of the Qinghai–Tibet Plateau. In addition, changes in the trend of human pressure before and after 2010 were analyzed to examine the influence of conservation policies on human pressure. Results showed that human pressure on KBAs and NNRs gradually increased from 1990 to 2017. Furthermore, the growth rates and mean values of human pressure in KBAs were higher than those in NNRs. After the implementation of conservation policies in 2010, the growth rates of human pressure on both KBAs and NNRs have significantly slowed, and the areas with negative growth in both KBAs and NNRs have gradually expanded. In addition to providing an understanding of the changing spatiotemporal trends of human pressure on KBAs, this study can serve as a reference to formulate policies for the improvement of the effectiveness of conservation.